Legal basis of administrative law and legal ways of providing personal security - Осипенко, Наталія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article the author makes analysis common theoretical terms, such as legal ways and the mechanism of legal regulation. Analysis the legislation material selects the row of features the administrative legal and law ways and the author gives the definition of the administrative legal and law ways in a sphere of providing personal security.